TOLERANSI ALA ACEH (INTOLERANSI):SEBUAH ANALISIS SENSE OF PLACE DALAM PENDIRIAN RUMAH IBADAH AGAMA MINORITAS DI ACEH - Faradilla Fadlia (Journal of Political Sphere, 2020)
AbstractThis paper aims to analyse how a sense of place helps to create definitions of tolerance and intolerance in Aceh. Banda Aceh is deemed to be one of the most intolerant cities in Indonesia, according to the results of a survey issued by the Setara Institute (2018). This paper proposes that Aceh, as a province that implements Islamic law with a majority Muslim population, creates a sense of place that influences the definition of tolerance. This paper asks: how does this sense of place influence the tolerance of the Acehnese towards efforts to establish places of worship for non-Muslims? Many Acehnese believe that they show tolerance towards non-Muslims who live in the region. However, this acceptance of the presence of non-Muslims in the province does not extend to providing space and support for religious activities and efforts to establish non-Muslim places of worship, as reflected in Qanun Number 4 of 2016, concerning 'Guidelines for the Maintenance of Religious Harmony and the Establishment of Places of Worship'. This paper draws upon in-depth interviews, informal interviews, focus group discussions, and other observations.Keywords: Intoleransi, Sense of Place, Religion, minority, Aceh